Training on making handwash Ag nanoparticle of Sesbania leaf extract for Fatayat NU - Wilda Amananti; K. Kusnadi; Meliyana Perwita Sari; Nur Alfia Fatmawati; Aldi Budi Riyanta (Journal of Community Service and Empowerment, 2023)
In order to strengthen the skills and creativity of Fatayat Nahdlatul Ulama (NU) members, Handwash soap making training is a useful activity.  Soap making training can provide Fatayat NU members with the opportunity to acquire new skills. In this training, participants will learn various techniques and methods in making quality soap. This community service activity can also provide information and knowledge to Fatayat NU women about making Sesbania leaf extract nanoparticle handwash soap. Based on the evaluation results, it shows an increase in the knowledge of Fatayat NU about making handwash. With an increase in the average value of pretest results from 40 and posttest 75 This community service is an effective means of disseminating information and knowledge about hygiene, health, and the importance of washing hands with soap.